LOST TRADITIONS, SILENCED CHILDHOODS: COLONIAL LEGACIES AND THE RECONSTRUCTION OF CHILD RIGHTS IN INDIA - Subla, Faraaz; Javaid Rashid (International Journal of Cultural and Social Science, 2025)
This study investigates the legacy of colonization on indigenous child-rearing practices and notions relating to childhood in India, conceptualizing this historical rupture as a driver for the erasure of culturally located modes of care, education, and protection. This study focuses specifically on colonial interventions that displaced family settings, alienated community caregiving, and imposed Eurocentric disciplinary and morally sanctioned practices; the British legal and educational legacy entrenched vernacular forms of childhood as pathological. This theoretical paper draws from postcolonial and decolonial childhood studies to examine how popular representations of children were located within pre-existing constructs of the child through a Victorian lens, missionary schooling, the deferral of the English legal system, and juvenile reformatories that made singular the plurality of parenting and knowing in terms of some wage-earning regions of the subcontinent. By analyzing legislative texts, educational policy records, and cultural artifacts, the study assumes a child shifting between a collective and a juridical subject of state power. In narrating such changes, I demonstrate that the contemporary child rights agenda in India, situated in a response to an international human rights framework, contains a legacy of colonial constructions of the child, the family, and development. While the Right to Education (RTE) Act and the Juvenile Justice (JJ) Act are formalized, they frequently occur in an epistemic fracture with local culture and knowledge. Through this research, it advocates for a renegotiation of the child rights discourse that aims not only to rectify structural injustices but also to reimagine care, kinship, and learning spaces, which have been irreparably silenced by epistemic colonization. By reclaiming the subaltern accounts of childhood, it reconstitutes a rights-based framework in cultural legitimacy and historical continuities. The erased traditions are not just remnants of past practice, but they are also sites of ethical relations and resilient communities, representing signposts for envisioning decolonized, inclusive, child-centred futures.